2020
DOI: 10.1002/cplu.202000220
|View full text |Cite
|
Sign up to set email alerts
|

Bis(α‐hydroxycycloalkyl)phosphine Oxides Obtained from White Phosphorus via Phosphine Oxide H3PO: Synthesis, Molecular Structure, Coordination Properties and Biological Activity

Abstract: This contribution is dedicated to Prof. Manfred Scheer on the occasion of his 65th birthday.Reaction of the electrochemically in situ from elemental white phosphorus generated phosphine oxide H 3 PO in a single electrochemical cell, supplied with lead cathode and aluminium anode, with cyclic ketones (cyclopentanone and cyclohexanone) results in formation of secondary phosphine oxides (bis (α-hydroxycyclopentyl)phosphine oxide 2 a, isolated yield 15 %, and bis(α-hydroxycyclohexyl)phosphine oxide 2 b, isolated y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our comprehensive evaluation of all nine derivatives revealed that the phosphine oxide derivatives (5-8) exhibit enhanced activity against the tested cancer cells in comparison to the aziridine phosphines (1-4) (Table 1). This is consistent with the literature reports indicating that the presence of bulky substituents on the phosphorus atom enhances biological activity [18,22,23]. It was also confirmed that aziridine should have a protected amino group to exhibit cancer cell viability inhibition, indicated by a lack of compound 9 activity, and Carraminana et al observed a similar effect [19].…”
Section: Reactive Oxygen Species Measurementsupporting
confidence: 91%
“…Our comprehensive evaluation of all nine derivatives revealed that the phosphine oxide derivatives (5-8) exhibit enhanced activity against the tested cancer cells in comparison to the aziridine phosphines (1-4) (Table 1). This is consistent with the literature reports indicating that the presence of bulky substituents on the phosphorus atom enhances biological activity [18,22,23]. It was also confirmed that aziridine should have a protected amino group to exhibit cancer cell viability inhibition, indicated by a lack of compound 9 activity, and Carraminana et al observed a similar effect [19].…”
Section: Reactive Oxygen Species Measurementsupporting
confidence: 91%
“…In the last few years, organometallic anticancer complexes bearing phosphine-containing chelating ligand have become a new approach to adjust the chemical and biological properties. A typical example is RAPTA family (e.g., RAPTA-C; Scheme , V ) containing 1,3,5-triaza-7-phosphatricyclo[3.3.1.1. ]­decane ligand and Ru–arene complexes, , which has been at an advanced preclinical trial .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, taking advantage of these stable structures as pseudo-bidentate ligands, several catalytic reactions have been developed. ,,,,,,,, In contrast, monodentate PA or phosphoryl ligand-coordinated complexes without the formation of quasi-chelate structures are relatively rare. Bulky SPO preligands tend to afford PA complexes, ,, although these preligands can also furnish quasi-chelate structures. ,, Bidentate NP­(O)H preligands also form quasi-chelate structures. , Phosphoryl complexes without intramolecular hydrogen bonding were formed as transient intermediates in transition metal-catalyzed reactions using SPOs as substrates. , Structurally defined Au 11 clusters with monodentate phosphoryl ligands were also reported . To utilize the cooperative effects of the PA ligand (or phosphoryl ligand) and the transition metal in catalysis, such as oxygenation shown in Scheme , SPO preligands that do not form strong intramolecular hydrogen bonding are required.…”
Section: Introductionmentioning
confidence: 99%